Computational vision and medical image processing VipIMAGE 2009 : proceedings of VipIMAGE 2009 : second ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing, Porto, Portugal, 14-16 October 2009 /: VipIMAGE 2009 : proceedings of VipIMAGE 2009 : second ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing, Porto, Portugal, 14-16 October 2009. (2010) - Unknown
No abstract available